Experience of health care utilization for inpatient and outpatient services among older adults in India - Mayanka Ambade; Rockli Kim; S.V. Subramanian (Elsevier, 2024)
Background: Patient experiences have not been documented at all India level among older adults for inpatient and outpatient services. We provide all-India and sub national estimates on six domains of patient experience, namely: waiting time, respectful treatment, clarity of explanation provided, privacy during consultation, treated by provider of choice, and cleanliness of facility. Methods: Unit records of adults aged 45 years and above for their inpatient (n = 4330) or outpatient (n = 33,724) service use were assessed from the Longitudinal Ageing Survey of India (LASI), conducted in 2017-18. We identified patient experience as negative if the respondent rated it as either "Bad" or "Very Bad" on a five-point Likert scale. We computed proportion of negative experience by socio-economic status, geographic location, and type of healthcare facilities. We used binary logistic regression to estimate predictors of negative patient experience, and a three-level logistic regression model to partition the total geographic variation of patient experiences. Findings: Most individuals rated their experience in all six domains as "Good". Negative experiences were higher among patients who used public facilities, specifically for waiting time and cleanliness of facility. Among inpatients, the higher-than-average negative experience was noted in the north and northwest, while among outpatients, it was higher in the northeast. The largest geographic variation in negative patient experience was attributable to the villages/CEBs for all domains in outpatient services and three domains of inpatient services, whereas states accounted for the other three inpatient domains. Interpretation: Majority of older adults rated their experience of healthcare use positively, but less for public health facilities.